Clinicopathological Features of Craniopharyngioma: A 15-Year Study From a Tertiary Care Center in Pakistan - Haroon, Saroona (Cureus, 2021)
Introduction Craniopharyngiomas (CPs) are benign neoplasms and most common suprasellar tumors. They are more frequent in children, contributing to a significant number of intracranial tumors in the pediatric population and are thought to be arising either from the epithelial remnant cells of the craniopharyngeal duct or from the adenohypophysis epithelium. Two subtypes of CPs exist, namely, adamantinomatous craniopharyngioma (ACP) and papillary craniopharyngioma (PCP). ACP is more common in children with a relatively aggressive clinical course and more frequent relapses than PCP. The study objective was to evaluate the clinicopathological features of CP in our population. Methods We conducted a retrospective observational study in the Department of Histopathology at Aga Khan Hospital, Karachi, Pakistan, over a period of 15 years, from January 2001 to December 2015. All CP cases were included in the study. A total of 207 cases were diagnosed during this period by histopathologists based on histologic features. All slides were retrieved, and diagnosis was confirmed after a reexamination of slides. Results We found that the mean age of diagnosis was 25.59±14.71 years, and the median follow-up time was 7 (3-19) years. The number of male patients was 136 (65.7%) and the number of female patients was 71 (34.3%). The most common tumor site was suprasellar (71.5%) followed by the sellar and temporal lobe (12.1% and 6.8%, respectively). The most common complaints were headache (21.7%), followed by loss of vision/decreased vision (16.4%) and vomiting (5.3%). The overall survival rate was 95.2% with a recurrence rate of 5.8%. A significant association of survival was noted with tumor recurrence. Conclusion CP is a rare brain tumor with good overall survival. We found a low recurrence rate of CP in our study. However, recurrence was found to be the most important factor determining survival in patients with CP.